2021
DOI: 10.3389/fpsyg.2021.628033
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From the First Wave of COVID-19: Work-Related Consequences, Clinical Knowledge, Emotional Distress, and Safety-Conscious Behavior in Healthcare Workers in Switzerland

Abstract: The coronavirus disease (COVID-19) imposes an unusual risk to the physical and mental health of healthcare workers and thereby to the functioning of healthcare systems during the crisis. This study investigates the clinical knowledge of healthcare workers about COVID-19, their ways of acquiring information, their emotional distress and risk perception, their adherence to preventive guidelines, their changed work situation due to the pandemic, and their perception of how the healthcare system has coped with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…This is in line with two studies, which were conducted before COVID-19 pandemic and reported a moderate stress level among nurses (Almazan et al 2019;Keykaleh et al 2018). In a more recent study 70% of the participants experienced emotional distress (Riguzzi and Gashi 2021). In this study they used one question on how worried the participants felt, because of the possibility of (1) "getting COVID-19 yourself," (2) "family/friends getting COVID-19," and ( 3) "numerous cases of death among old and sick people due to COVID-19", which can be rated by a 4-point Likert scale.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with two studies, which were conducted before COVID-19 pandemic and reported a moderate stress level among nurses (Almazan et al 2019;Keykaleh et al 2018). In a more recent study 70% of the participants experienced emotional distress (Riguzzi and Gashi 2021). In this study they used one question on how worried the participants felt, because of the possibility of (1) "getting COVID-19 yourself," (2) "family/friends getting COVID-19," and ( 3) "numerous cases of death among old and sick people due to COVID-19", which can be rated by a 4-point Likert scale.…”
Section: Discussionsupporting
confidence: 89%
“…This is surprising, as the Austrian government recommended in mid-March that all unnecessary health treatments, e.g. knee replacement surgery, should be postponed, which should have decreased the number of hospital patients (Federal Ministry of Social Affairs, Health, Care and Consumer Protection, Bundesministerium für Soziales Gesundheit Pflege und Konsumentenschutz 2020); however, a more recent study on COVID-19 among healthcare workers reported that nearly one third stated that they have to work more than usual (Riguzzi and Gashi 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On June 13, 2020, 41,303 cases and 1422 deaths were reported nearly at the peak of the first pandemic wave [ 4 ]. On September 2, 2020, 99,280 cases and over 5400 deaths were reported [ 5 ] and in mid-October, 2020, the second pandemic wave was announced [ 6 ] and reached its peak in December 2020 and January 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of association between caring for patients with COVID-19 and anxiety scores could be explained by HCPs' perception that such experience may help them grow as a person and professional [72]. Better knowledge of the disease and health safety measures [7,90], the experience gained since the outbreak of the pandemic [91], and the increased availability of PPE [7] may have strengthened the confidence of Quebec HCPs caring for patients with COVID-19, thus reducing their anxiety level.…”
Section: Discussionmentioning
confidence: 99%